CURRENT TRENDS IN BANKING ACTIVITIES IN THE EU: ASSESSMENT OF FACTORS IMPACTING PROFITABILITY - Svitlana Tkalenko; Roksoliana Liubachivska; Yurii Onopriienko; Yaroslav Stetsyk; Olena Petukhova (Фінансово-кредитна діяльність: проблеми теорії та практики)
The article examines current trends in banking activities within EU countries and their long-term impact on the banking sector. It focuses on the role of banks in the economic development of the EU at the present stage. The authors highlight the contribution of banks to economic growth through the mobilization and redistribution of financial resources. The study emphasizes that ensuring the stability and efficiency of the banking system in the EU is achieved through the harmonization and joint regulation of the financial market, which is a cornerstone of the European integration process. The identified modern trends in banking activities within the EU include: continuous improvement of the regulatory mechanism in the European Union; transformational and modernization processes in EU banking, aligning with global economic trends; and the development of online and digital banking. The authors conclude that the current stage of banking development involves a shift in banking technologies, the introduction of innovations, and changes in market behaviour models. Econometric modelling was conducted to assess the impact of factors on profitability levels. The most significant factors influencing the profitability of EU banks were identified as consolidated banking leverage and the growth rate of real GDP. The findings indicate a gradual decrease in profitability in the short term, with prospects for growth in the future. The model underwent all validation stages and demonstrated high predictive quality. The object of the study is banking activities in EU countries and their influence on European economic development. The subject of the study encompasses the theoretical and practical aspects of banking development in EU countries, modern banking trends, and future prospects.